The Influence of Personality, Leadership Style, and the Decision-Making Process on Employee Performance - Fahrul Kahfi; Muliyadi Hamid; Sri Adrianti Muin (Newinera Publisher, 2024)
This research aims to examine the influence of personality, leadership and decision making on employee performance at PDAM Makassar City. The method used in this research is a structural equation model with a total of 66 respondents consisting of men and women. Based on data analysis, it was found that personality and leadership had a positive and significant effect on employee performance, while decision making did not show a significant effect. Validity and reliability tests show that all indicators are suitable for use, with Cronbach alpha values above 0.70. The data normality test shows a normal distribution, and the multicollinearity test shows there is no correlation between the independent variables. The heteroscedasticity test does not show symptoms of heteroscedasticity, which indicates a good regression model. The T test shows that personality and leadership variables have a significant effect on performance, while decision making does not have a significant effect. The F test shows that the independent variables simultaneously have a significant effect on employee performance. The coefficient of determination (R2) value of 0.677 indicates that the model has a strong relationship between the independent variable and the dependent variable. Based on these findings, it is recommended to improve personality training programs, leadership qualities, and improve decision-making processes to improve overall employee performance.